The Influence of Hypo Kinesis and Frequency Strain of a Car Ride on Mechanical Functions of Axial System Changes - Kateřina van der Kamp; Richard Billich; Karel Jelen; Josef Zeman (Karolinum Press, 2015)
The Influence of Hypo Kinesis and Frequency Strain of a Car Ride on Mechanical Functions of Axial System Changes In our measurements, we used TVS method to detect mechanical changes of axial system. These mechanical changes can be base for discomfort feeling during monotonous driving in the car. The TVS method is based on the use of consequent application of continuously changing harmonic stimuli, which periodically differ between 5 Hz and 160 Hz, to the vertebrae C7 and L5. This wave is carried through the axial system and its acceleration on the spinous processes between C7 and S1 is scanned with the help of accelerometric sensors. According to the measured data, it is possible to identify changes of the mechanical properties of the human spine before and after applying hypo kinesis and frequency loading by the car ride. The research results proved the fact, that the TVS method is suitable for detection of the mechanical changes of axial system. It was also proved that changes caused by a monotonic and frequency loading influence the way of waves transfer through the axial system of the observed participants. From our data results, that we can compare the subjects more intraindividual than interindividual. We found out that healthy and flexible spine oscillates like elastic bar. It is able to absorb more mechanical energy with higher elasticity and the spinal joints are more flexible. The resonant frequency of the healthy and flexible spine lies between 40 and 60 Hz or higher. In most of the cases we found higher damping and lower transmission of the vibrations after the loading. By some of the subjects we can find different reaction in thoracic and lumbar spine to the loading. Vliv hypokinézy a frekvenční zátěže na změnu mechanických vlastností axiálního systému při jízdě v automobilu V našem experimentu jsme použili metodu TVS k detekci mechanických změn axiálního systému. Tyto mechanické změny mohou být podkladem pro pocit diskomfortu během monotónního zatížení během jízdy v automobilu. Metoda TVS je založena na aplikaci harmonického buzení plynule se měnícího od 5 Hz do 160 Hz na obratle C7 a L5. Toto vlnění se přenáší podél axiálního systému a akcelerometrickými snímači je snímáno zrychlení všech trnových výběžků obratlů, kterými se vlnění šíří mezi C7 až S1. Na základě naměřených dat lze vyhodnotit změnu mechanických vlastností páteře před a po hypokinéze a frekvenčním zatížení při jízdě v automobilu. Náš výzkum prokázal, že metoda TVS je vhodná pro detekci změn mechanických vlastností axiálního systému. Dále bylo prokázáno, že změny způsobené monotónním a frekvenčním zatížením ovlivňují způsob přenosu vlnění axiálním systémem subjektů. Z našich naměřených dat vyplývá, že můžeme subjekty srovnávat spíše intraindividuálně než interindividuálně. Zjistili jsme, že zdravá a flexibilní páteř osciluje jako elastická tyč a je schopna absorbovat více mechanické energie a spojení na páteři jsou více flexibilní. Rezonanční frekvence zdravé a flexibilní páteře se při našich měřeních objevuje mezi 40 a 60 Hz nebo výše. Ve většině případů nacházíme po jízdě v automobilu vyšší tlumení a nižší přenos vibrací. U některých subjektů se objevuje odlišná reakce na zatížení v hrudní a bederní páteři.